Building A Framework for Selecting Appropriate External Voluntary Standard (EVS) in the United Kingdom (UK) Food Sector Using Eight Exemplars - Olusina, Adedoyin (2011)
ABSTRACT The aim of this research is to build a framework that will guide CR managers in selecting an appropriate external voluntary standard (EVS) in United Kingdom (UK) food sector. The objective of the research was to know how eight exemplars in the UK food sector prioritise issues, stakeholders and EVS. A conceptual induction method based on theory building from multiple case studies was used in this research. Secondary data was collected from CSR reports and websites of eight exemplars selected for the research. The case companies were selected based on their listings in at least of one indexes such as FTSE4Good, Dow Jones Sustainability Index and Business in the Community Corporate Responsibility Index. The case companies are referred to as exemplars because they are well ahead of their peers in areas of sustainability. Data was analysed using within case and cross case analysis, in order to establish develop building blocks for the framework. Examples of the issues, stakeholders and EVS that were found to be of high priority to exemplars are forced labour, child labour, deforestation of the rain forest, packaging materials, employees, NGOs, government, suppliers, Global Reporting Initiative (GRI) , ISO 14001 and Roundtable on Sustainability of Palm Oil (RSPO). And those found to be of low priority to exemplars are child trafficking, security of employment, legislators, trade associations, ISO26000 and Global Social Compliance Programme (GSCP). This research have introduced a systematic EVS selection guidance for CR managers in the UK food sector, and also creating an awareness on high and low priority issues, stakeholders, and EVS in the UK food sector. Keywords: Exemplars, External Voluntary Standards, Framework